Find f(x)•g(x)

f(x) = 3x - 1

g(x) = x^2 + 4

Skip to content# Find f(x)•g(x)f(x) = 3x – 1g(x) = x^2 + 4

Mathematics ##
Comments (4) on “Find f(x)•g(x)f(x) = 3x – 1g(x) = x^2 + 4”

### Leave a Reply Cancel reply

Find f(x)•g(x)

f(x) = 3x - 1

g(x) = x^2 + 4

It says in the questions that it is 6.5?

1. the question is asking you to multiply the two function expressions together

2. so all we do is (3x - 1)(x² + 4) which gives you 3x³ + 12x - x² - 4

addition

step-by-step explanation:

[tex]Will pay paypal money to whom answers all! answer first[/tex]

The answer in photo

Don't forget put heart ♥️

[tex]Find f(x)•g(x) f(x) = 3x - 1 g(x) = x^2 + 4[/tex]